2016
DOI: 10.1038/srep30673
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Fecal Microbiota of Patients with HIV-1 Infection: An Observational Study in A Chinese Population

Abstract: The available evidence suggests that alterations in gut microbiota may be tightly linked to the increase in microbial translocation and systemic inflammation in patients with human immunodeficiency virus 1 (HIV-1) infection. We profiled the fecal microbiota as a proxy of gut microbiota by parallel barcoded 454-pyrosequencing in 67 HIV-1-infected patients (32 receiving highly active antiretroviral therapy [HAART] and 35 HAART naïve) and 16 healthy controls from a Chinese population. We showed that α-diversity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
172
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(202 citation statements)
references
References 64 publications
(135 reference statements)
24
172
5
1
Order By: Relevance
“…Samples were collected from the mid-stream stool in the present study, which is less convenient than swabbing, but may retain Several studies have found that a-diversity was significantly decreased in untreated HIV-infected patients [9,14]. While Ling et al [20] showed no difference in bacterial alpha diversity of gut microbiota between HIV-infected patients and healthy controls, another study found a clear decrease in overall bacterial diversity after effective HAART [5,8]. In this study, HIV-infected individuals had lower levels of Prevotella, a genus of Gram-negative anaerobic bacteria previously grouped in the genus Bacteroides and Bacteroides.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Samples were collected from the mid-stream stool in the present study, which is less convenient than swabbing, but may retain Several studies have found that a-diversity was significantly decreased in untreated HIV-infected patients [9,14]. While Ling et al [20] showed no difference in bacterial alpha diversity of gut microbiota between HIV-infected patients and healthy controls, another study found a clear decrease in overall bacterial diversity after effective HAART [5,8]. In this study, HIV-infected individuals had lower levels of Prevotella, a genus of Gram-negative anaerobic bacteria previously grouped in the genus Bacteroides and Bacteroides.…”
Section: Discussionmentioning
confidence: 83%
“…Although little is known about alterations of gut microbiota in Chinese patients infected with HIV, Ling et al researched the issue in Zhejiang province in eastern China. The authors observed that a-diversity indices did not differ significantly between the healthy controls and patients infected with HIV-1, while the proportion of Firmicutes/Bacteroidetes increased significantly in HIV-1-infected patients [20]. Sun et al [21].…”
Section: Introductionmentioning
confidence: 99%
“…Low‐grade systemic inflammation characterized by activated T cells, inflammatory cytokines, endotoxaemia and gut bacteria translocation has been linked to poor disease outcomes and increased mortality . Studies have demonstrated that HIV infection is associated with intestinal dysbiosis characterized by increased Prevotella and reduction in Bacteroides . Recent studies suggest that increased Prevotella in HIV is a driver for persistent inflammation in the gut leading to mucosal dysfunction and systemic inflammation .…”
Section: Gut Dysbiosis Triggered By Hivmentioning
confidence: 99%
“…Even the dysbiosis in the gut or the respiratory tract has been linked to alterations in immune responses and to disease development [50]. Also the severity of malaria seems to be modulated by the composition of the gut microbiota [51], and in patients with human immunodeficiency virus 1 (HIV-1) infection a linkage between alterations in the gut microbiota and the increase in microbial translocation and systemic inflammation could be confirmed [52]. In addition, researchers were able to determine a link between the intestinal microbiome and hepatitis B virus infection given that the gut microbiota composition was shown in a hydrodynamic transfection mouse model to contribute to the age dependence of hepatitis B virus clearance and immunity [53].…”
Section: Applications Of Germfree Rodent Models In Biomedical Researchmentioning
confidence: 99%